(untitled) (Texas Journal of Medical Science, 2025)
Uterine diseases encompass a wide range of conditions that can significantly impact women’s health, fertility, and overall well-being. This overview examines common uterine disorders, including fibroids, endometriosis, adenomyosis, endometrial hyperplasia, and uterine cancer. The causes, symptoms, diagnostic methods, and treatment options for each condition are discussed. Special emphasis is placed on preventative measures, such as regular screenings, lifestyle modifications, hormonal management, and awareness of risk factors. Early detection and appropriate management are crucial for reducing morbidity and improving outcomes associated with uterine diseases. The aim is to provide a concise guide to understanding uterine diseases and promoting proactive strategies for prevention and early intervention